International human rights and their enforcement in Africa - Mbondenyi, Morris Kiwinda (LawAfrica Pub., 2011)
Whilst the establishment of the African human rights system was a good gesture that signalled the recognition of the value and essence of international human rights in the continent, a continuous study of the system has become necessary. This is particularly in light of the fact that the continent is in desperate need of well established and effective regional human rights enforcement mechanisms. At the moment, the regional human rights system is stuck between prospects and pitfalls because of the gap that exists between the promise of human rights and their actual realisation. By all means, this trend needs to be reversed. The main objective and purpose of this book is to underscore the challenges besetting the effective enforcement of international human rights law in Africa and the prospects and promises of an effective regional human rights system.